Effect of different factors on patient perception of surgical discomfort in third molar surgery - Giselle Emilãine da Silva Reis; Robson Diego Calixto; Maria Fernanda Pivetta Petinati; Juliana Feltrin de Souza; Erika Calvano Kuchler; Delson João da Costa; Daniel Bonotto; Nelson Luis Barbosa Rebellato; Rafaela Scariot (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract: The aim of this study was to evaluate patient perception of surgical discomfort in third molar surgery and the association with clinical variables and polymorphisms associated with the FKBP5, SLC6A4, and COMT genes. This cross-sectional observational study was carried out on 196 participants aged between 18 and 64 years at the Federal University of Paraná in 11 months. The intensity of surgical discomfort was assessed using the QCirDental questionnaire. Data on surgical and individual procedures were also cataloged. The oral health related quality of life was assessed by the Oral Health Impact Profile questionnaire (OHIP-14). The DNA sample was obtained from cells of the oral mucosa. Five markers of the FKBP5, SLC6A4, and COMT genes were genotyped. The data were submitted to statistical analysis with a significance level of 5%. Women reported greater intensity of discomfort associated with third molar surgery compared to men (p = 0.001). In the recessive model, the AA genotype of the rs3800373 marker was associated with greater surgical discomfort (p = 0.026). Therefore, women and individuals of the AA genotype for the rs3800373 marker in the FKBP5 gene reported greater surgical discomfort associated with third molar surgery.